The luck of the draw the role of lotteries in decision making - Stone, Peter, 1971 Oct. 14- (New York ; Oxford : Oxford University Press, 2011)
A prominent scholar once noted that lotteries in politics & society--to break vote ties, assign students to schools, draft people into the military, select juries--are 'at first thought absurd, & at second thought obvious.' Lotteries have been part of politics since the Greek & Roman times, & they are used widely in American politics today.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Lotteries; Decision making; Political science -- Decision making